2019
DOI: 10.3390/su11102821
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Mountain-Plain Breeze Circulation in Eastern Chengdu, China

Abstract: The spatiotemporal structure and evolution of the thermally-induced mountain-plain breeze circulation in the Longquan Mountain, eastern Chengdu, are studied by the WRF-ARW model based on a two-day case. Turbulence characteristics are also examined to better understand the local circulation of the area. Simulation results show that the 2 m temperature distribution of the plain and mountain areas is peculiar due to the occurrence of the temperature inversion. The plain and mountain breezes can be predicted expli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…The average 98th percentile wind gust in the coastal areas is 10.6 m/s, which is 10% higher than the wind gust in the noncoastal area (9.5 m/s). This result is consistent with [6,7] stated that the sea-land and mountain-valley systems significantly affect the wind system. Further, this study showed the consistency of the higher wind gust speed of sea-land breeze compared to mountain valley wind gust speed.…”
Section: The 98 Th -Percentile and 50-year Return Level Wind Gust Speedsupporting
confidence: 92%
“…The average 98th percentile wind gust in the coastal areas is 10.6 m/s, which is 10% higher than the wind gust in the noncoastal area (9.5 m/s). This result is consistent with [6,7] stated that the sea-land and mountain-valley systems significantly affect the wind system. Further, this study showed the consistency of the higher wind gust speed of sea-land breeze compared to mountain valley wind gust speed.…”
Section: The 98 Th -Percentile and 50-year Return Level Wind Gust Speedsupporting
confidence: 92%
“…The WRF is a globally used NWP model for analyzing atmospheric processes and extreme weather conditions such as cold waves, heat waves, and precipitation [32]. Tian and Miao (2019) simulated mountain plain breeze circulation using BouLac PBL (planetary boundary layer), Noah + UCM land surface, and MM5 surface layer schemes in the WRF model in eastern Chengdu, China [33]. Mohan and Gupta (2018); Gunwani and Mohan (2017); Sathyanadh, Prabha et al (2017) simulated the meteorological variables using the number of physical WRF schemes in various parts of India to boost the WRF results [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the Noah LSM is one of the most widely used land surface schemes for research studies, as well as for weather and regional climate modeling [24]. In this regard, Noah LSM has not only been coupled to the WRF model but also to the operational North American Mesoscale (NAM) Forecast System, the Global Forecast System (GFS), and other National Centers for Environmental Prediction (NCEP) modeling systems [19,25,26]. On the other hand, the Noah-MP model is an evolutional version of the original Noah LSM.…”
Section: Introductionmentioning
confidence: 99%